(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: Noise-Induced Hearing Loss (NIHL) remains a prevalent occupational health issue in industrial sectors. This study aimed to evaluate the longitudinal progression of hearing thresholds in municipal workers exposed to noise levels exceeding 85 dB(A) and to determine the impact of specific risk stratification on auditory health. Methods: A Retrospective Longitudinal Cohort Study was conducted on 23 male municipal workers over a two-year surveillance period (2023–2025). Participants were stratified into Group A (Gardeners, n=5) and Group B (Drivers, n=18) categories based on job profiles. Pure-tone audiometry was analyzed according to Health and Safety Executive (HSE 2021) guidelines. Statistical analysis included Wilcoxon signed-rank test and Mann–Whitney U tests for group comparisons. Results: The cohort exhibited a statistically significant deterioration in mean hearing thresholds over the study period. Wilcoxon signed-rank test comparing mean high-frequency thresholds (3–4–6 kHz) between 2023 and 2025 yielded p < 0.001. By 2025, 47.8% (n=11) of the workforce met the criteria for clinical referral (Category 3). A distinct disparity was observed between exposure groups: 100% (n=5) of Group A workers progressed to Category 3, compared to only 33.3% (n=6) of Group B workers (p = 0.042). Conclusion: Group A demonstrated significantly accelerated hearing loss compared to drivers (B), validating the need for stratified risk management. The findings support the implementation of a shortened 6-month audiometric review cycle for high-risk groups.